The Balfour Declaration - Guediri, Kaoutar (السفير العربي, 2016)
After the "The McMahon-Hussein correspondence: phase one of the partition process" and "The Sykes-Picot agreements – phase two of the partition process", this article is the sequel of the roundup, presenting The Balfour Declaration, in context and detail.